2017
DOI: 10.3892/or.2017.5533
|View full text |Cite
|
Sign up to set email alerts
|

Induction of galectin-1 by TLR-dependent PI3K activation enhances epithelial-mesenchymal transition of metastatic ovarian cancer cells

Abstract: The expression of different toll-like receptors (TLRs) on tumor cells has been associated with disease aggressiveness, treatment resistance, and poor prognosis. The phosphatidylinositol 3-kinase (PI3K)/AKT pathway is considered critical for cancer cell survival and proliferation. Thus, we investigated the effect of TLR-stimulated PI3K activation on the epithelial-to-mesenchymal transition (EMT) of primary (Caov-3) and metastatic (SK‑OV‑3) epithelial ovarian cancer cell lines in this study. TLR engagement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Interestingly, the cisplatin-resistant ovarian cancer cells transfected with Gal-1 siRNA were more responsive to the negative effects of cisplatin than those transfected with the control siRNA. These findings [ 71 ], and those of others [ 55 , 69 , 70 , 76 ], suggest that if a targeted disruption of Gal-1 expression/function in tumor tissue or the immediate tumor microenvironment could be obtained, it may be a plausible therapeutic option for cisplatin-resistant ovarian cancer.…”
Section: Galectin-1 (Lgals1)mentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, the cisplatin-resistant ovarian cancer cells transfected with Gal-1 siRNA were more responsive to the negative effects of cisplatin than those transfected with the control siRNA. These findings [ 71 ], and those of others [ 55 , 69 , 70 , 76 ], suggest that if a targeted disruption of Gal-1 expression/function in tumor tissue or the immediate tumor microenvironment could be obtained, it may be a plausible therapeutic option for cisplatin-resistant ovarian cancer.…”
Section: Galectin-1 (Lgals1)mentioning
confidence: 75%
“…In a study by Park et al [ 76 ], they were investigating the differences in toll-like receptor (TLR) mediated phosphoinositol 3 kinase (PI3K) signaling activity in CAOV3 and SKOV3 ovarian cancer cell lines. The investigators had postulated that Gal-1 might be a promising candidate for downstream targeting of the TLR/PI3k mediated signaling pathway in metastatic ovarian cancer.…”
Section: Galectin-1 (Lgals1)mentioning
confidence: 99%
“…Zhang et al, 2015). TLR-mediated PI3K activation modulates the invasion and metastasis of ovarian cancer through the production of galectin-1, suggesting that inhibition of the p110 isoform may be a promising therapeutic approach against metastatic ovarian cancer (Park, Chung, & Kim, 2017). Another study revealed that TLRs may be a target for treatment of ovarian cancer (Muccioli & Benencia, 2014 (2015) found that melatonin therapy reduced TLR2 levels, while it suppressed the ovarian cancer-associated increase in the levels of the following proteins: TLR4, MyD88, NF-kB p65, inhibitor of NFkB α (IkBα), IKK-α, TNF receptor-associated factor 6 (TRAF6), TRIF, IRF3, interferon β (IFN-β), tumor necrosis factor α (TNF-α), and interleukin (IL)-6.…”
Section: Melatonin In Cancermentioning
confidence: 99%
“…TLRs stimulation is functionally associated with tumor growth and progression (16). We also reported that TLR4-mediated TLR5/7-mediated PI3K activation triggers epithelial-mesenchymal transition of ovarian cancer cells through WAVE3-dependent mesothelin or OCT4/SOX2 expression PI3K activation controls the invasion and metastasis of ovarian cancer through the production of galectin-1 (17). However, the underlying mechanism and association of PI3K for inducing mesothelin in TLR5/7-activated ovarian cancer cells remains unclear.…”
Section: Introductionmentioning
confidence: 95%